2013
DOI: 10.1038/ncomms3965
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the role of the Smoothened cysteine-rich domain in Hedgehog signalling

Abstract: Smoothened (Smo) is a member of the Frizzled (FzD) class of G-protein-coupled-receptors (GPCRs), and functions as the key transducer in the Hedgehog (Hh) signalling pathway. Smo has an extracellular cysteine-rich domain (CRD), indispensable for its function and downstream Hh signalling. Despite its essential role, the functional contribution of the CRD to Smo signalling has not been clearly elucidated. However, given that the FzD CRD binds to the endogenous Wnt ligand, it has been proposed that the Smo CRD may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 56 publications
0
72
0
Order By: Relevance
“…In vertebrates, 7-keto-27-OHC (Table 1) functions as an agonist at the SMO CRD 16 . Although Drosophila Smo does not respond to 20(S)-OHC 73,74 , the glucocorticoid budesonide ( Table 1) binds both Drosophila and human SMO CRDs using NMR chemical shift perturbations and can inhibit SMO activity 76 . The precise role of the SMO CRD in endogenous Hedgehog signaling is a key question.…”
Section: Smo Regulation Through Its Crdmentioning
confidence: 99%
See 1 more Smart Citation
“…In vertebrates, 7-keto-27-OHC (Table 1) functions as an agonist at the SMO CRD 16 . Although Drosophila Smo does not respond to 20(S)-OHC 73,74 , the glucocorticoid budesonide ( Table 1) binds both Drosophila and human SMO CRDs using NMR chemical shift perturbations and can inhibit SMO activity 76 . The precise role of the SMO CRD in endogenous Hedgehog signaling is a key question.…”
Section: Smo Regulation Through Its Crdmentioning
confidence: 99%
“…7a,25-OHC neither competes with 20(S)OHC for binding to SMO nor activates Hh signaling 16 . Multiple small molecules are capable of modulating the SMO CRD 75,76 . In vertebrates, 7-keto-27-OHC (Table 1) functions as an agonist at the SMO CRD 16 .…”
Section: Smo Regulation Through Its Crdmentioning
confidence: 99%
“…Curiously, the Drosophila Smo CRD does not bind to 20(S)-OHC (63), but it and human Smo CRD were recently shown to bind to the glucocorticoid budesonide (Fig. 4B), suggesting that sterol binding by the Smo CRD may be a conserved feature of Hh signaling (69). Glucocorticoids represent an interesting class of Smo modulators as both inhibitors and activators of the Hh pathway have been found with glucocorticoid scaffolds, and budesonide inhibits WT Smo, SmoD473H, and SmoM2 equally well, ideal features for a Smo-targeting drug (70).…”
Section: Smoothened: Cysteine-rich Domainmentioning
confidence: 99%
“…To test this hypothesis and gain structural and functional understanding of this domain, we determined the structure of the Drosophila Smo CRD by solution NMR spectroscopy. Our findings show that Smo CRD is a structured domain predominated by alpha helical secondary structures stabilized by disulfide bonds and maintains the tertiary fold similar to the FzD CRD [147]. The residues highlighted in yellow correspond to the "site 1" and the residues highlighted in green correspond to the "site 2" binding site in FzD-Wnt interaction.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis we analyzed the interaction between the glucocorticoid Bud and the Drosophila and human Smo CRD by NMR CSP experiments [143,155]. Our results demonstrate that Bud binds to both Drosophila and human Smo CRD, albeit with different binding affinities [147]. † Furthermore, we generated the modelled structure of Drosophila Smo CRD in complex with the inhibitory glucocorticoid Bud, which showed that Bud docks in a conserved hydrophobic pocket in Smo CRD.…”
Section: Introductionmentioning
confidence: 99%